A Model of Housing Quality Determinants (HQD) for Affordable Housing - Chohan, Afaq Hyder; Che Ani, Adi Irfan; Sha, Bhai Khan; Awad, Jihad; Jawaid, Arif; Mohd Tawil, Norngainy (Penerbit Universiti Sains Malaysia, 2015)
This research identifies the design quality determinants and parameters for affordable housing in a developing metropolis, Karachi, Pakistan. The absence of quality housing in Karachi has resulted in a variety of factors including policy failure, violation of bylaws, housing scarcity and more low quality housing. The combination of these factors has resulted in poor housing design and construction and has lowered the overall quality of housing. Homeowners (end-users) experience unplanned maintenance and repairs. This study provides a design quality model for use as a survey tool among professionals and end-users. This study resulted in a table of 24 quality determinants marked as Housing Quality Determinants (HQD) grouped into eight sections. This research concludes that the existing design quality of affordable housing in Karachi could be enhanced by resolving problems related to design, construction, services, site development, neighbourhood and sustainability. The HQD model provides a platform for developing quality indicators of housing design and an opportunity for local and international design and construction professionals to rethink design in the context of housing quality. This article provides the development of the HQD framework (model).